IbM PENGEMBANGAN USAHA KRIPIK PISANG DALAM MENDUKUNG TERWUJUDNYA SIDOARJO SEBAGAI KOTA UKM DI INDONESIA - Hana Catur Wahyuni; Athika Sidhi Chyana; Mulyono Mulyono (Jurnal Abadimas Adi Buana, 2018)
Gelam Village is located in Kec Candi, Sidoarjo Regency, Â± 5 km from the center of Sidoarjo city. Gelam Village is one of the settlement destinations for Sidoarjo mudflow victims. Most of the residents of Gelam village have a search for factory employees and entrepreneurs. The field of entrepreneurship that most of the villagers in Gelam are involved in is the food sector, one of which is the manufacture of banana chips. In its development there were problems related to the production, administration and marketing processes. These three factors currently hamper the development of banana chips business in Gelam village, especially experienced by IbM partners, the targets and outcomes expected from the implementation of community service programs are: the availability of banana cutting machines for the production process of banana chips in Gelam village, Sidoarjo Regency. , the availability of an administration system so that it can be used to find out the business development of banana chips. Therefore, to overcome these problems, the solution offered through the implementation of IbM is: the solution to the problem of the production process is through IbM will be made a banana cutting machine, the solution to administrative problems is through the preparation of a good and correct financial administration, so that it can be used to see the development of businesses and access to funds to banks, the solution to the problem of marketing is through label making that attracts consumers.